1995
DOI: 10.1073/pnas.92.11.5102
|View full text |Cite
|
Sign up to set email alerts
|

A C-terminally-anchored Golgi protein is inserted into the endoplasmic reticulum and then transported to the Golgi apparatus.

Abstract: Unlike conventional membrane proteins of the secretory pathway, proteins anchored to the cytoplasmic surface of membranes by hydrophobic sequences near their C termini follow a posttranslational, signal recognition particleindependent insertion pathway. Many such C-terminallyanchored proteins have restricted intracellular locations, but it is not known whether these proteins are targeted directly to the membranes in which they will ultimately reside. Here we have analyzed the intracellular sorting of the Golgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 25 publications
4
95
0
1
Order By: Relevance
“…Deletion of the Inp54p hydrophobic tail resulted in a cytoplasmic distribution of the protein, consistent with previous observations that the C terminus of tail-anchored proteins contains the membrane targeting information (38,45,47,48,59,60). The last 13 amino acids of Inp54p also direct GFP to the ER.…”
Section: Discussionsupporting
confidence: 73%
“…Deletion of the Inp54p hydrophobic tail resulted in a cytoplasmic distribution of the protein, consistent with previous observations that the C terminus of tail-anchored proteins contains the membrane targeting information (38,45,47,48,59,60). The last 13 amino acids of Inp54p also direct GFP to the ER.…”
Section: Discussionsupporting
confidence: 73%
“…EEA1 interacts with the GTP-bound form of Rab5p via a small N-terminal domain containing a zinc finger and through a C-terminal fragment adjacent to the so-called FYVE finger. In contrast, Sys3p, which shares with EEA1 the extended ␣-helical regions but does not contain sequences related to its Rab5p-interacting regions, does not interact with Ypt6p or its GTPasedeficient mutant Ypt6(Q69L)p. Giantin, a 376-kDa, rod-shaped protein bound to the cytoplasmic surface of Golgi membranes (Linstedt et al, 1995), has been reported recently to have a role in COPI vesicle docking (Sö nnichsen et al, 1998). Likewise, the Sys3p-related Uso1 protein, which like Sys3p is only partially membrane associated, is needed for the docking of ER-derived vesicles to the cis-Golgi compartment (Sapperstein et al, 1996;Cao et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immunofluorescence analysis of COS cells demonstrated Golgi staining of the endogenous TMEM59, which overlapped with the well characterized Golgi markers giantin (cis-medial Golgi) (31,56) and p230 (trans-Golgi and TGN) (57) (Fig. 5, A and B).…”
Section: Tmem59mentioning
confidence: 99%